Prevalence of treatment resistance and clozapine use in early intervention services. Issue 5 (September 2020) - Stokes, Imogen; Griffiths, Siân Lowri; Jones, Rowena; Everard, Linda; Jones, Peter B.; Fowler, David; Hodgekins, Joanne; Amos, Tim; Freemantle, Nick; Sharma, Vimal; Marshall, Max; Singh, Swaran P.; et al.
Abstract : Background: Treatment resistance causes significant burden in psychosis. Clozapine is the only evidence-based pharmacologic intervention available for people with treatment-resistant schizophrenia; current guidelines recommend commencement after two unsuccessful trials of standard antipsychotics. Aims: This paper aims to explore the prevalence of treatment resistance and pathways to commencement of clozapine in UK early intervention in psychosis (EIP) services. Method: Data were taken from the National Evaluation of the Development and Impact of Early Intervention Services study ( N = 1027) and included demographics, medication history and psychosis symptoms measured by the Positive and Negative Syndrome Scale (PANSS) at baseline, 6 months and 12 months. Prescribing patterns and pathways to clozapine were examined. We adopted a strict criterion for treatment resistance, defined as persistent elevated positive symptoms (a PANSS positive score ≥16, equating to at least two items of at least moderate severity), across three time points. Results: A total of 143 (18.1%) participants met the definition of treatment resistance of having continuous positive symptoms over 12 months, despite treatment in EIP services. Sixty-one (7.7%) participants were treatment resistant and eligible for clozapine, having had two trials of standard antipsychotics; however, only 25 (2.4%) were prescribed clozapine over the 12-month study period. Treatment-resistant participants were more likely to be prescribed additional antipsychotic medication and polypharmacy, instead of clozapine. Conclusions: Prevalent treatment resistance was observed in UK EIP services, but prescription of polypharmacy was much more common than clozapine. Significant delays in the commencement of clozapine may reflect a missed opportunity to promote recovery in this critical period.